Tolerance to the antinociceptive and hypothermic effects of morphine is mediated by multiple isoforms of c-Jun N-terminal kinase. Issue 6 (13th April 2016) - Yuill, Matthew B.; Zee, Michael L.; Marcus, David; Morgan, Daniel J.
Abstract : The abuse and overdose of opioid drugs are growing public health problems worldwide. Although progress has been made toward understanding the mechanisms governing tolerance to opioids, the exact cellular machinery involved remains unclear. However, there is growing evidence to suggest that c-Jun N-terminal kinases (JNKs) play a major role in mu-opioid receptor regulation and morphine tolerance. In this study, we aimed to determine the potential roles of different JNK isoforms in the development of tolerance to the antinociceptive and hypothermic effects of morphine. We used the hot-plate and tail-flick tests for thermal pain to measure tolerance to the antinociceptive effects of once-daily subcutaneous injections with 10 mg/kg morphine. Body temperature was also measured to determine tolerance to the hypothermic effects of morphine. Tolerance to morphine was assessed in wild-type mice and compared with single knockout mice each lacking the JNK isoforms (JNK1, JNK2, or JNK3). We found that loss of each individual JNK isoform causes impairment in tolerance for the antinociceptive and hypothermic effects of daily morphine. However, disruption of JNK2 seems to have the most profound effect on morphine tolerance. These results indicate a clear role for JNK signaling pathways in morphine tolerance. This complements previous studies suggesting that the JNK2 isoform is required for morphine tolerance, but additionally presents novel data suggesting that additional JNK isoforms also contribute toward this process.